Phylogenetic analysis of rove beetle subfamily Staphylininae (Coleoptera: Staphylinidae) based on the morphology of preimaginal stages, with description of larva and pupa of Algon sphaericollis - Chong Li; Liang Tang (Arthropod Systematics & Phylogeny)
Staphylininae, a highly diverse subfamily of rove beetles (Coleoptera: Staphylinidae), has been the subject of numerous phylogenetic studies primarily based on molecular genetics and adult morphology. This work represents an initiation of phylogenetic studies using complete immature morphology, encompassing eggs, larvae and pupae, for 27 genera of Staphylininae and two outgroups. Our findings indicate that the combination of data from all three immature stages is more phylogenetically informative than the larval data alone. The resulting maximum parsimony tree partially aligns with previous research, although certain tribal-level issues remain unresolved. Through morphological comparisons, we revealed the morphological diversity of protibia, paratergites and parasternites of abdominal segment I as examples of parallel and mosaic evolution within Staphylininae larvae. We conducted detailed character analyses to provide explanations for these phenomena. Furthermore, this study provides the first morphological data for several species of Staphylinini. Notably, we present a comprehensive study of the morphology of immature stages of Algon sphaericollis Schillhammer, 2006, the first species of the recently established subtribe Algonina with known larva. Additionally, we provide the larval morphology data for six other species: Eucibdelus sp., Platydracus pseudopaganus pseudopatricius (Müller, 1926), Platydracus marmorellus (Fauvel, 1895), Saniderus cooteri Rougemont, 2015, Saniderus sp., and Philonthus spinipes Sharp, 1874.